Regulation of Women’s Sexuality and Reproduction in Public Health Institutions in Mexico - Orozco Galván, Aldo Iván (Revista Punto Género, 2025)
Family Planning (FP) is considered one of the main strategies to prevent maternal and infant morbidity and mortality and is regulated by various public policies in Mexico, which are reflected in the National Health Card. This study examines how the Card functions as an instrument to regulate women’s reproductive health care, aligning it with the objectives of public health policies. Using institutional ethnography, the research mapped how institutional dynamics shape women’s experiences during their health care. The findings reveal that the Card operates as a device that regulates not only medical care processes but also women’s presence in health institutions. This control often translates into institutional violence, undermining women’s autonomy and dignity by subordinating their individual needs to the objectives of family planning policies.